Language Style Used by The Main Character in Hala: A Sociolinguistic Study - Salsabila, Jovanka; Lestari, Kurnia; Fiscarina, Canna Vionitaretami (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
Everyone has their own unique way of communicating through language. This language style is used depends on the circumstances of a conversation, for example by the context and conversation participants. Language style is a sociolinguistic study that examines how people communicate with others who speak in a range of styles. The object of this research is the Hala movie, a movie that tells about a Muslim teenager who lives in America and has to face between two cultures. This study focuses on the analysis of language style used by the main character in Hala movies and several factors that influence the main character to speak in a different language style. This movie is analyzed using Martin Joos’s language style theory, the five clock theories of frozen style, formal style, consultative style, casual style, and intimate style, as well as Janet Holmes’s theory of social factors why people speak with different language styles. This study uses a qualitative descriptive method in which the data are collected from the movie. The results of this research indicate that the main character used different language styles, and some factors influenced her to speak in different language styles. There were 49 data found of language style used by the main character, consultative style with 7 data, casual style with 18 data, intimate style with 11 data, formal style with 13 data, and 0 data for frozen style. However, there were 62 social factors that influenced Hala to speak with different language style, participants with 28 data, 7 settings, and 27 contexts.